NBP0702 surface sediment sample information and images - Jacobs, Stanley; Leventer, Amy (IEDA: US Antarctic Program Data Center, 2021)
This dataset contains images and field description of Smith-McIntyre sediment grab samples from Expedition NBP0702 between the Ross Sea and the Amundsen Sea.